Effect of addition titanium dioxide nanoparticles as acrylic resin denture base filler on cytotoxicity - Ardhianing Hardita; Titik Ismiyati; Endang Wahyuningtyas (Faculty of Dentistry, Universitas Gadjah Mada, 2019)
Denture base material should have a good level of biocompatibility. Acrylic resin is frequently used as a denture base material, however it has a disadvantage of producing residual monomer. Residual monomer is known to have a cytotoxicity effect. Titanium dioxide (TiO2) nanoparticles are used as fillers due to their biocompatibility and ability to enhance the mechanical properties of acrylic resin. The addition of the material to acrylic resin could affect the amount of residual monomer. The aim of this study was to examine the effect of the addition of TiO2 nanoparticles as acrylic resin denture base filler on the cytotoxicity in fibroblast cells. The samples consisted of 24 heat cured acrylic resins in disc shape (5 mm in diameter and 2 mm in thickness), divided into 4 groups (n = 6): three groups given treatment with0.5%, 1%, 2% TiO2, respectively and one control group. Cell viability was measured with MTT assay. The results were tested with one way ANOVA with 95% confidence level followed by LSD post hoc test. The results showed that the highest percentage of cell viability was found in the treatment group of 0.5% TiO2 with value of 91.83 ± 1.75%, while the lowest value was seen in the treatment group of 2% TiO2 with value of 79.38 ± 3.34%. Significant differences were shown between the treatment groups of 0.5% and 2% TiO2, as well as between the control and treatment group with 2% TiO2. The conclusions of this research are the addition of TiO2 nanoparticles as acrylic resin denture base filler has an effect on cytotoxicity; the addition of 0.5% TiO2 nanoparticles filler results in lower cytotoxicity on fibroblast cells compared to the addition of 1% and 2% TiO2.